PENGARUH METODE PROBLEM BASED LEARNINGDAN METODE INQUIRY TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PADA SISWA KELAS VII MTS MIFTAHUL MUBTADIIN - Siti Mukarromah; Sunardjo; Dian Eka Indriani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
Civics Education is a course that aims to educate students to foster morals and become a good citizen, which are expected to be realized in daily life, both in the school environment and outside the school environment. Civics education should be able to shape activeness , creativity, and intelligent thinking of students in solving any existing problem by way of consensus agreement in accordance with the 4th-point Pancasila precepts namely "Democracy led by wisdom discretion in deliberation and representation". Civics is a lesson about government and civic obligations relating to the state or among citizens'. This study uses a quantitative quasi-experimental type of research by using one variable to know the learning outcomes, namely, affective, cognitive and psychomotor, which aims to determine the effect and differences of the Problem Based Learning and Inquiry methods on the results. Based on the data analysis, it can be concluded that citizenship education learning with Problem Based Learning (PBL) method is better than Inquiry learning. There are differences in student learning achievement after using the Problem based learning method in Civics VIII A/B MTs Miftahul Mubtadiin.